Beneish M-Score Analysis as a Detector of Financial Report Fraud in Building Construction Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) - Rosalia , Selvia Erninda; Bakhtiar , Yohan; Ahmad Saifi Athoillah (JBS Nexus, 2026)
Transparency in the construction sector which is vulnerable to manipulation due to performance pressure and large project risks as shown by PT Wijaya Karya (WIKA), highlighting the urgency to evaluate financial accountability in construction companies. This study aims to implement Beneish M-Score method to detect potential financial fraud in building construction sub-sector listed on Indonesia Stock Exchange during 2019-2024 and to identify the financial ratios that most influence the probability of fraud using binary logistic regression. This study used quantitative descriptive method with secondary data from the Indonesia Stock Exchange website. The population included all building construction sub-sectors listed on IDX during 2019-2024, with four samples; PT Wijaya Karya Tbk (WIKA), PT Waskita Karya Tbk (WSKT), PT Adhi Karya Tbk (ADHI) and PT PP Tbk (PTPP). The results of the study showed that manipulation indication of financial statement which was fluctuative when PT Wijaya Karya Tbk (WIKA) and and PT PP Tbk (PTPP) identified as manipulators several times, while PT Waskita Karya Tbk (WSKT) and PT Adhi Karya Tbk (ADHI) remained the most consistent non-manipulators. The Total Accruals to Total Assets (TATA) ratio proved significant in detecting fraud based on the binary logistic regression test. Manipulation might occur at any time depending on internal conditions and external pressures. Companies are needed to improve internal audits and implement strict reporting policies each period to prevent potential financial statement manipulation.